EFFECTIVENESS AND IMPLICATIONS OF PROVISION OF COVID-19 ASSISTANCE FOR MSMES IN TANJUNGPINANG CITY - Marlinda, Charly; Satriadi, Satriadi; Risnawati, Risnawati; Agusven, Tubel (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study was to analyze the effectiveness of providing covid-19 assistance to MSMEs in Tanjungpinang City using measurement indicators in the form of timeliness and accuracy in making choices, as well as to analyze the impact caused by the provision of economic and social assistance to the community in Tanjungpinang City. This study uses a descriptive method with a qualitative approach. The results of this study indicate that the data collection process to the distribution of COVID-19 assistance in Tanjungpinang City has been effective in terms of timeliness and accuracy in making choices. In addition, Covid-19 assistance can help the community's economy, especially the MSMEs in Tanjungpinang City, but it causes social impacts in the form of conflicts between MSMEs and the city government, in this case the manpower office, cooperatives and micro-enterprises and the government.